Diet, microbiota and autism - Reaño, Ernesto (2023)
Nutrition is a fundamental element in autistic people but not different from what it can be for the general population. Unscientific perspectives suggest that a special type of diet will "recover" the person from autism or that intervening on their microbiota will diminish their characteristics. This has its origin in “biomedical” positions that were born of frauds (such as Wakefield and vaccines) or beliefs derived from them. We now know that autism is not a disease but a life condition associated with atypical neurodevelopment. For this reason, there is no cure, although there are interventions and adjustments in the environment that can improve the quality of life for those autistic people who are in a situation of disability. Following food treatments that have not been tested can generate deficits that affect the growth and health of the autistic person. This is not to say that there are no gastrointestinal problems that co-occur with autism. However, these problems must be treated independently and in no case as those that cause autism. This not only has no evidence, but also diverts the focus of attention, especially in non-speaking autistics who often cannot effectively communicate their ailments.